Tackling a Post-COVID-19 Cholecystectomy Waiting List: Are We Meeting the Challenge? - Mohammed Hamid; Neginsadat Mirtorabi; Abdul Ghumman; Ayesha Khalid; Mohamed Saleem Noormohamed; Spyridon Kapoulas; Rishi Singhal; Rajwinder Nijjar; Martin Richardson; Tom Wiggins (Medicina, 2023)
Background and Objectives: The COVID-19 pandemic has led to a tremendous backlog in elective surgical activity. Our hospital trust adopted an innovative approach to dealing with elective waiting times for cholecystectomy during the recovery phase from COVID-19. This study aimed to evaluate trends in overall cholecystectomy activity and the effect on waiting times. Materials and Methods: A prospective observational study was undertaken, investigating patients who received a cholecystectomy at a large United Kingdom hospital trust between February 2021 and February 2022. There were multiple phased strategies to tackle a 533-patient waiting list: private sector, multiple sites including emergency operating, mobile theatre, and seven-day working. The correlation of determination (R2) and Kruskal–Wallis analysis were used to evaluate trends in waiting times across the study period. Results: A total of 657 patients underwent a cholecystectomy. The median age was 49 years, 602 (91.6%) patients had an ASA of 1-2, and 494 (75.2%) were female. A total of 30 (4.6%) patients were listed due to gallstone pancreatitis, 380 (57.8%) for symptomatic cholelithiasis, and 228 (34.7%) for calculous cholecystitis. Median waiting times were reduced from 428 days (IQR 373–508) to 49 days (IQR 34–96), R2 = 0.654, p < 0.001. For pancreatitis specifically, waiting times had decreased from a median of 218 days (IQR 139–239) to 28 (IQR 24–40), R2 = 0.613, p < 0.001. Conclusions: This study demonstrates the methodology utilised to safely and effectively tackle the cholecystectomy waiting list locally. The approach utilised here has potential to be adapted to other units or similar operation types in order to reduce elective waiting times.